Discourse in ritual studies - Schilderman, Hans, 1959- (Empirical studies in theology, 2007)
Discourse in Ritual Studies invites you to enter a conversation on the topic of liturgy from the perspective of ritual studies. Since liturgical topics are not among the most frequently addressed issues in ritual studies, this volume supplies a need for studies of public worship that take into account the multidisciplinary and innovative research in ritual studies while dealing with basic issues of religious studies and theology. The contributing authors share an action-oriented and empirical interest in ritual studies while not losing sight of perennial and normative questions that characterize the study of liturgy. Thus, a valuable discourse unfolds that opens up new opportunities for worship research in ritual studies. Contributers are: Johannes van der Ven, Ronald Grimes, Chris Hermans, Jacques Janssen, Jean-Pierre Wils, Georg Essen, Aad de Jong, Thomas Quartier, Remco Robinson, Lieve Gommers, Irene Houwer, and Hans Schilderman.